Associations between IL-17A G/A-rs2275913 and IL 23R A/G-rs11209026 gene polymorphisms and severe coronavirus disease 2019 (COVID-19) - Goda, Asmaa M; Abdelrahman, Mona M; Fattouh, Mona; Hemdan, Shimaa B; Abdel Baset, Asmaa A; Younis, Mustafa A; Abuzied, Enas K A; Mahmoud, Mahmoud G; Shafik, Noha S (The Egyptian journal of immunology, 2023)
Severe COVID-19 disease was linked to a severe proinflammatory response and cytokine storm interleukin 17 (IL-17) is one of these cytokines, was associated with severe acute lung injury and multiorgan dysfunction. Single nucleotide polymorphisms (SNPs) in genes coding IL-17 can affect level of IL-17 hence its role in diseases. Also, SNPs in IL-23 R which control IL-23 is the main activator of IL-17 production. This study aimed to determine whether the IL-17A (G/A-rs2275913), IL-23R (A/G rs11209026) SNPs and serum levels of IL-17 were related to the risk of severe COVID-19. This case-control study included 120 confirmed COVID-19 patients, divided into two categories according to the severity of the disease and 74 normal subjects as controls. COVID-19 patients were SARS-CoV-2 positive by a reverse transcription-polymerase chain reaction and subjected to full clinical examinations, routine laboratory tests, and radiographic evaluations. The IL-17 levels were assessed using ELISA method, and genotyping of IL-17A (197 A/G; rs2275913) and IL-23R rs11209026 (A/G) was performed by the TaqMan Genotyping Assay. There were no differences in the distribution of IL-17A or IL-23R genotypes between COVID-19 groups and the control group (p=0.93 and p=0.84, respectively). Severe COVID-19 patients had significantly higher IL-17 serum levels than non-severe COVID-19 (p=0.0001). The GG genotypes of IL-17A were significantly higher in severe COVID-19 patients (p=0.004). Multivariate logistic regression analysis revealed that AG, GG genotypes of IL-17 and IL-17A were independent predictors of COVID-19 disease severity (p < 0.0001, p=0.06 and p=0.04, respectively). ROC curve analysis for IL-17, as predictor of severe COVID-19 disease revealed a sensitivity of 87.9% and specificity of 66.1% at a cutoff point of 114 pg/ml with AUC = 0.799. In conclusion, these findings indicated that IL-17 may be considered a marker of severe COVID-19. IL-17A SNPs may have a role in COVID-19 severity. IL-23R SNPs had no role in COVID-19.